Molecular phylogenetic analysis of six Ribes L. species from Kazakhstan based on DNA barcodes of nuclear and chloroplast genomes - Almerekova, Shyryn; Yermagambetova, Moldir; Sumbembayev, Aidar; Ivashchenko, Anna; Imanbayeva, Akzhunis; Turuspekov, Yerlan (Fundamental and Experimental Biology, 2025)
Ribes L. species are of significant ecological and economic importance. Their berries are rich in functional metabolites, which contribute to both their nutritional value and potential health benefits. However, the genus is taxonomically complex and requires comprehensive studies to resolve its phylogenetic relationships. In this study, we sequenced three genetic regions – the internal transcribed spacer (ITS) and the chloroplast genes matK and rbcL to investigate the phylogeny of Ribes species collected in Kazakhstan. There were six species analyzed Ribes janczewskii Pojark., Ribes aureum Pursh, Ribes graveolens Bunge, Ribes nigrum L., Ribes rubrum L., and Ribes saxatile Pall., collected from various regions of Kazakhstan. Phylogenetic trees were constructed using the Maximum Likelihood method implemented in IQ-TREE. The aligned sequence lengths were 686 base pairs (bp) for ITS, 750 bp for matK, and 498 bp for rbcL. Among these, the ITS region showed the highest number of polymorphic sites (219), followed by matK (195) and rbcL (50). Nucleotide diversity (Pi) was also highest in the ITS region (0.0735), nearly double that of matK (0.03703), and substantially greater than rbcL (0.01378). The nucleotide sequences of ITS, matK, and rbcL obtained from this study have been deposited in the GenBank database of the National Center for Biotechnology Information (NCBI) under accession numbers PV702933-PV702944, PV730383-PV730394, and PV730395-PV730406, respectively. The newly generated sequence data provide a valuable foundation for future phylogenetic and evolutionary research in Ribes.